Women and gender in Islam: Historical roots of a modern debate - Ahmed, Leila (Yale University Press., 1992)
Explores the historical roots of the debate about women in Islamic societies by tracing the developments in Islamic discourses on women and gender up to the present. The book describes the gender systems in place in the Middle East both before and after the rise of Islam.
Keywords: 1800-1899; 1900-1999; approches et analyses; asie; discipline; fem1000; femmes* musulmanes; féminisme islamique; genre; histoire; identités LGBTQIA2+; islam; moyen-âge; orient; premier cycle; périodes historiques; rapports de domination; rapports sociaux de sexe; religion; ressource en ligne; régions géographiques; science des religions; sciences humaines; sexisme; sociologie; syrie; systèmes d'oppression; thématiques; théologie; voiles islamiques